Repeated 0.2-Gy γ-Ray Irradiation Attenuates the Inflammatory Process and Endotoxin Damage Induced by Lipopolysaccharides. Issue 2 (21st June 2019) - Dong, Suhe; Qian, Wen; Liu, Tingting; Liu, Hu; Du, Jicong; Zhao, Hainan; Gao, Fu; Cai, Jianming
Endotoxin damage is an acute, multi-organ disease, the most typical symptoms of which are liver injury and inflammatory cytokine storm. Endotoxin tolerance is described as the pretreatment of lipopolysaccharides (LPS) before the toxin invasion, which is consistent with the adaptive response induced by low-dose radiation (LDR). In this study, we verified that LDR could resist the endotoxin damage by suppressing the increase of inflammatory cytokines, including interleukin 6, tumor necrosis factor, and NO, to improve the survival and relieve the inflammatory cell infiltration, in which low dose of LPS performed consistently with LDR.